2006
DOI: 10.1016/j.euroneuro.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic treatment with fluvoxamine and paroxetine during adolescence on serotonin-related behavior in adult male rats

Abstract: Selective Serotonin Reuptake Inhibitors (SSRIs) are designed to treat adults, but are increasingly prescribed for adolescents. SSRIs might cause permanent changes in serotonin-related behavior in adolescents, since their serotonergic system is still developing.Male Wistar rats were treated with paroxetine (15 mg/kg p.o.) or fluvoxamine (30 mg/kg p.o.) throughout adolescence. After a washout period their behavior in the elevated plusmaze, prepulse inhibition test, Forced swimming test and elevated T-maze were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 53 publications
(61 reference statements)
0
51
0
Order By: Relevance
“…The benzodiazepine anxiolytic diazapam exhibited no effects on apomorphine-induced PPI deficits in rats (de Jong et al , 2006; Rigdon, 1991) but it has been found to increase PPI in C57BL6J, a mouse strain that has naturally low PPI (Ouagazzal et al , 2001). With regard to the anticonvulsant mood stabilizer valproic acid, Ong et al (Ong et al , 2005) found that it had no effect on PPI in C57BL/6J mice, whereas Flood et al (Flood et al , 2009) reported that it increased PPI in DBA.2 mice, another strain with naturally low PPI.…”
Section: Discussionmentioning
confidence: 99%
“…The benzodiazepine anxiolytic diazapam exhibited no effects on apomorphine-induced PPI deficits in rats (de Jong et al , 2006; Rigdon, 1991) but it has been found to increase PPI in C57BL6J, a mouse strain that has naturally low PPI (Ouagazzal et al , 2001). With regard to the anticonvulsant mood stabilizer valproic acid, Ong et al (Ong et al , 2005) found that it had no effect on PPI in C57BL/6J mice, whereas Flood et al (Flood et al , 2009) reported that it increased PPI in DBA.2 mice, another strain with naturally low PPI.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible as well, that PE populations may differ in some neurophysiological dimension, as compared to depressed or other clinical populations for whom SSRIs are commonly prescribed. However, post SSRI persistence of biological changes or adaptations can by no means be ruled out [8], are supported by animal studies [50][51][52], and thus ought to be a cause for concern.…”
Section: Critiquementioning
confidence: 99%
“…Even though there are many children and adolescents with psychiatric disorders (Emslie and Mayes, 2001), decisions regarding the use of antidepressants in young people (such as the SSRIs) are still largely based on data from adults (Manfridi et al, 1992; de Jong et al, 2006). Efficacy measurements in humans recommend SSRIs as the initial medication of choice for young individuals in depression and for improving obsessive-compulsive disorder (OCD; Doogan and Caillard, 1988; Alderman et al, 1998; Emslie and Mayes, 2001; Moreno et al, 2006).…”
Section: Introductionmentioning
confidence: 99%